Portal Hypertension - Inda D. Arif; Mardjanis Said; E.M Halimun (Indonesian Pediatric Society, 1978)
A case of portal hypertension in a 9-year-old Indonesian female child is presented. The diagnosis was made by demonstrating oesophageal vanices radiologically and surgically, and by measuring the portal venous pressure. Portocaval side to side shunt was done resulting in diminishing of the oesophageal varices, disappearance of hypersplenism, and a normal portal venous pressure. Continuous observation is recommended despite the relative good prognosis.